The Effect of Long Exposure Reed Diffuser Essential Oil Plumeria alba on Cortisol Levels of Male Wistar Rats - Siska Siska; Tahyatul Bariroh; Supandi Supandi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Stress can occur due to a person's inability to respond to a stressor, resulting in bodily or mental disorders. Anxiety can be characterized by increased levels of cortisol, which is regulated by the Hypothalamus-Pituitary-Adrenaline (HPA-axis). Aromatherapy is a therapy using essential oils that give a distinctive aroma to plant parts such as flowers, roots, leaves, and stems. Aromatherapy can be done through a reed diffuser. The frangipani (Plumeria alba) is one of the plants in Indonesia that has a particular scent in its flowers. This study aims to determine the effect of prolonged exposure to P. alba essential oil reed diffuser on cortisol levels in rats. Twenty-four rats were divided into four groups: the control group without exposure to a reed diffuser for 5 and 10 days and the other group with exposure for 5 and 10 days. Each blood was drawn through the retro-orbital, centrifuged to obtain serum, and tested using LC-MS to determine cortisol levels. The group with ten days of essential oil exposure showed lower cortisol levels. It can be concluded that the duration of aromatherapy exposure is connected to cortisol levels and that aromatherapy can be utilized as a stress-reduction therapy.